Характеристика пігментного апарату інтенсивних сортів озимої пшениці української селекції - Маслюківська, О.В.; Прядкіна, Г.О.; Соколовська-Сергієнко, О.Г.; Стасик, О.О. (Фактори експериментальної еволюції організмів, 2015)
Aims. Characteristics of plant pigment apparatus that determine their photosynthetic activity may be related to the grain yield. The comparative analysis of the content and the total amount of chlorophyll in organs of different varieties of winter wheat and assessment of their correlations with grain yield were the purposes of this study. Methods. Chlorophyll contents in leaves, stems and ears were determined by Wellburn (1994). Chlorophyll indices (ChlI, g chl/m2 ) were calculated as the product of chlorophyll concentration in organs and their mass and number of shoots per unit area of soil. Results. Comparative evaluation of chlorophyll in the organs of modern wheat varieties of Ukrainian selection showed that the maximum difference in the leaves did not exceed 15–20 % and in the stems and ears – 35–45 %. The differences between the most contrasting varieties in the magnitude of ChlI were higher – up to 60 %. The closest correlation with grain productivity were found for ChlI calculated for leaves, stems and whole shoots, whereas the total amount of chlorophyll in the ears correlated with yield weakly. Conclusions. It was revealed that grain productivity of winter wheat is largely determined by the total amount of chlorophyll in the leaves and stems in the reproductive period of ontogenesis. Keywords: Triticum aestivum L., plant organs, chlorophyll, index of chlorophyll.